Inflation Targeting in Latin America - Adolfo Barajas; Roberto Steiner; Leonardo Villar; Cesar Pabon (Inter-American Development Bank (IDB), 2014)
Estimation of conventional Taylor rules for Brazil, Chile, Colombia and Peru shows that central banks increase their repo rate in response to increases in the output gap and, except in Peru, to deviations of inflation expectations from target. Using a Markov-Switching methodology, it is found that, in the presence of external shocks, Chile, Colombia and Peru temporarily abandoned their conventional reaction function. The Taylor Rule is expanded and variables are included related to exchange rate misalignments and to domestic credit developments; limited evidence is found that countries have used some form of integrated inflation targeting. There is strong evidence that intervention in F/X markets is determined by exchange rate misalignments rather than by exchange rate volatility and that most countries seem particularly concerned with a strong currency. Central banks appear to have pursued an inflation objective using a standard Taylor rule and an exchange rate objective through interventions in the F/X market.
Keywords: E31; E52; E61; 330